Impact of coastal development on mangrove distribution in Cherating Estuary, Pahang, Malaysia - Ahmad, Zuhairi; Mohamad Suharni, Muhammad Luqman; Taib, Siti Noor Aifa; Shammodin, Muhammad Shaheed (Penerbit UTM Press, 2019)
This study examined the impact of various coastal developments on mangrove cover along the Cherating Estuary, Pahang, Malaysia between 1997 and 2016. Series of Landsat imageries at Cherating Estuary have been analyzed using supervised classification. Over 19.99% (26.275 ha) of mangrove cover was degraded along the Cherating estuary from its total area of 131.642 ha during the past 20 years. The expansion of development or urban area can be observed in 1997 (27.93 ha) and in 2016 (111.02 ha), showing an increase by 297.0% in 20 years. We identified several causes of mangrove degradation, including mangrove clearing to commercial or residential area, and aquaculture activities. Cherating is one of the main tourism attractions in Pahang. The pace of coastal development throughout the estuary and the coast area had suppressed the mangroves propagation over the years. Long term monitoring of mangrove ecosystems is essential to ensure the survival and sustainability of mangrove associated biodiversity.